Investigation of Ni- and Co-Based Bifunctional Electrocatalysts for Carbon-Free Air Electrodes Designed for Zinc-Air Batteries - Emiliya Mladenova; Miglena Slavova; Borislav Abrashev; Valentin Terziev; Blagoy Burdin; Gergana Raikova (Emerging Science Journal, 2023)
Ni- and Co-oxide materials have promising electrocatalytic properties towards the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR), and attract with low cost, availability, and environmental friendliness. The stability of these materials in alkaline media has made them the most studied candidates for practical applications such as a gas diffusion electrode (GDE) for rechargeable metal-air batteries. In this work, we propose a novel concept for a carbon-free gas GDE design. A mixture of catalyst (Co3O4, NiCo2O4) and polytetrafluoroethylene was hot pressed onto a stainless-steel mesh as the current collector. To enhance the electrical conductivity and, thus, increase ORR performances, up to 70 wt.% Ni powder was included. The GDEs produced in this way were examined in a half-cell configuration with a 6 M KOH electrolyte, stainless steel counter electrode, and hydrogen reference electrode at room temperature. Electrochemical tests were performed and coupled with microstructural observations to evaluate the properties of the present oxygen electrodes in terms of their bifunctionality and stability enhancement. The electrochemical behavior of the new types of gas-diffusion electrodes, Ni/Co3O4 and Ni/NiCo2O4, shows acceptable overpotentials for OER and ORR. Better mechanical and chemical stability of electrodes consisting of Ni/NiCo2O4 (70:30 wt.%) was registered. Doi: 10.28991/ESJ-2023-07-03-023 Full Text: PDF